Right parietal lesions, unilateral spatial neglect, and the egocentric frame of reference - Chokron, Sylvie (NeuroImage (Orlando, Fla.), 2003)
Recently, the hypothesis has been proposed that the crucial mechanism leading to neglect is the disturbed transformation of sensory input into a supramodal egocentric frame of reference (ER), which causes in turn a deviation of this reference frame toward the side ipsilateral to the brain lesion. This egocentric coordinate system is normally centered on the midsagittal plane, but a unilateral brain lesion may cause a deviation of the egocentric reference due to an imbalance between the differentially lateralized neural processes which build this representation. Although neglect signs are often defined in an egocentric frame, and an ER shift may be observed in some right-brain-damaged patients (RBD), I present here several data that rule out any causal link between the deviation of the egocentric reference and the presence and/or severity of left-neglect signs in RBD patients.